PENGARUH KOMUNIKASI INTERPERSONAL PETUGAS KESEHATAN TERHADAP PENGETAHUAN PASIEN BPJS MENGENAI RUJUKAN DI PUSKESMAS PB SELAYANG 2 MEDAN - Barus, Darwita Juniwati; Rajagukguk, Desy Lustiyani (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2023)
Health care referral system implemented in phases in accordance with medical needs, from health care first level and second level. medical health care at this level can only be given if the participant gets a referral from the primary facility. This reference is only given if the patient requires specialist health services and primary health facilities designated to serve participants. This reference is only given if the patient requires specialist health services and primary health facilities designated to serve participants. if the disease can not be handled in the secondary health facilities, the participant may be referred to a tertiary care facility. Lack of interpersonal communication is very influential in patients' knowledge about the implementation of the referral system. Patients feel cumbersome if you want to get a referral to hospital services require a referral clinic. This is due to the lack of interpersonal communication that is openness, empathy, being supportive, positive attitude and equality. This study aims to determine the effect of interpersonal communication of health workers towards patients' knowledge about the reference BPJS in Puskesmas PB Selayang 2 Medan. Population in this research is patient referral BPJS participants in November 2023 in Puskesmas PB Selayang 2 Medan, as many as 408 people. This type of research is descriptive analytic observational with cross sectional design. The sample is patient referral BPJS participants as many as 40 people. Data were collected through questionnaires and interviews. Data were analyzed using Chi-Square test at α <5%. Health workers in interpersonal communication in Puskesmas PB Selayang 2 Medan. majority less as many as 23 people (57.5%) and minorities well and as many as 17 people (42.5%). From the results of the bivariate analysis (chi-square) that there is a p-value (0.031) <α (0.05) no significant relationship between interpersonal communication of health workers towards patients' knowledge about the reference BPJS in Puskesmas PB Selayang 2 Medan. Suggested to the officer interpersonal health centers to improve knowledge so that patients' knowledge about the referral BPJS better.